Re-imagining Science Education During COVID-19 Pandemic: Role of Teachers, Students, and Parents - Saraf, Ankit; Nagpal, Surbhi (SCHOOL SCIENCE, 2021)
The COVID-19 pandemic necessitates educators and teachers to think about novel teaching-learning methods, which enable deeper understanding and active involvement of students in their learning process. Given the nature of science, it is essential to design and create learning experiences that promote inquiry-based learning at home, nurture curiosity, and encourage learners to develop scientific understanding through reflection. There is a fear that virtual learning environments, both synchronous or asynchronous, can open doors for a more passive, lecture-based science pedagogy due to the unavailability of resources and support at home for most children in India. This paper re-envisions and outlines the roles that different stakeholders can play in creating a nurturing environment for science education at home through a short activity plan. This disquisition argues that virtual learning environments offer a broad scope for inquiry based, investigative, and interactive science learning through systematic and equitable collaboration between teachers, students, and parents.